Unraveling Vincent Mosko's Thoughts on the Commodification of Content, Audience and Workers: A New Phenomenon of the Digital Age in Indonesia - Marsefio Luhukay; Udi Rusadi (Communication Science Department - Petra Christian University, 2023)
This paper in the form of a scientific article discusses Vincent Mosko's thoughts on commodification in three main dimensions, namely content, audience, and workers. The concept of commodification is a subject of debate in the contemporary world, especially in the context of media and communication. This paper presents a critical analysis of Mosko's thinking on how the process of commodification has shaped and changed mindsets and practices in these three important aspects. First, this article reviews the concept of content commodification in the digital age. Mosko highlighted how content, which was initially individual and personal, underwent transformation into a commodity that could be monetized by industry players and social media platforms. This discussion covers the use of content as a means of marketing by companies and influencers, as well as its impact on the quality and integrity of the information presented. Secondly, this article explores Mosko's views on the commodification of audiences. In his perspective, the audience has gone from being mere recipients of messages to consumers directed and manipulated by marketing strategies. Mosko identifies how audience profiles are used to improve advertising effectiveness and how their engagement is measured in the context of marketing and sales. Third, this paper looks at how Mosko's approach in formulating the commodification of workers, especially in the creative and media sectors. Through literature analysis, this article highlights the workings of labor exploitation in the creative industries, including the role of digital platforms in shaping working conditions and influencing the sharing of economic value among workers. The results of the analysis in this article show how Vincent Mosko's thinking provides deep insight into the complexity and consequences of the process of commodification of content, audiences, and workers in the digital age. Further understanding of these concepts is expected to provide a foundation for academics, media practitioners, and policymakers to address the challenges and potential negative impacts arising from commodification in the world of media and communication.